Study of Pre Engineered Steel Building: Exploring the Advantages and Practicality of Pre-Engineered Steel Buildings (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The scientific-sounding term pre-engineered buildings came into being in the 1960s. The pre-engineered steel building system construction has great advantages to the single storey buildings, practical and efficient alternative to conventional buildings. It helps in reducing steel quantity, also increases atheistic view of structure.